Entrepreneurship: A new perspective - Thomas Grebel (Routledge, 2004)
The entrepreneur has been neglected over the years in formal economic theorizing. Previously there has been only eclectic theories such as human capital theory and network dynamics which discuss certain perspectives of entrepreneurial behaviour. This insightful book closes this gap in entrepreneurship literature. Inspired by modern physics, author Thomas Grebel brings together an evolutionary methodology, along the way implicating quantum, graph, and percolation theory. Here, Grebel has provided a synthesis of all the main theories of entrepreneurship. Taking an interdisciplinary approach to the subject, this fascinating book opens up new ideas in modelling and the original thinking contained within will be of interest to all those working in the area of business and management as well as those in economics.
Keywords: 330; Entrepreneurship; Ökonomische Ideengeschichte